Mathematical literacy of senior high school students on different multiple intelligences groups - Idris Iskandar; W. Wahyudin; S. Suhendra; R. Ramlah; Yusi Ardiyanti (Research and Development in Education (RaDEn), 2024)
Mathematical literacy is one of the mathematical skills that must be mastered. However, students' mathematical literacy in Indonesia is still fairly low. This study aimed to analyze and describe the mathematical literacy of senior high school students on different multiple intelligences groups in solving PISA problems. The research method used was qualitative with a case study design. The research subjects were 15-year-olds 10th-grade students in one of the senior high schools in Karawang, Jawa Barat. The subjects consisted of two students in the linguistic intelligence group and two students in the logical-mathematical intelligence group who were selected through a purposive sampling technique. Data collection techniques were carried out by filling out a multiple intelligence questionnaire, PISA test, and interviews then analyzed by reducing data, presenting it, and drawing conclusions. The results showed that: 1) students in the linguistic intelligence group are able to interpret the problem, but not able to formulate and employ mathematics to the problem; and 2) students in the logical-mathematical intelligence group are able to employ mathematics and interpret the problem, but not able to formulate the problem. The results emphasize the necessity for customized instructional strategies that address students' different multiple intelligences.